The microbiota-gut-brain axis and neurodevelopmental disorders - Wang, Qinwen; Yang, Qianyue; Liu, Xingyin (Protein & cell, 2023)
The gut microbiota has been found to interact with the brain through the microbiota-gut-brain axis, regulating various physiological processes. In recent years, the impacts of the gut microbiota on neurodevelopment through this axis have been increasingly appreciated. The gut microbiota is commonly considered to regulate neurodevelopment through three pathways, the immune pathway, the neuronal pathway, and the endocrine/systemic pathway, with overlaps and crosstalks in between. Accumulating studies have identified the role of the microbiota-gut-brain axis in neurodevelopmental disorders including autism spectrum disorder, attention deficit hyperactivity disorder, and Rett Syndrome. Numerous researchers have examined the physiological and pathophysiological mechanisms influenced by the gut microbiota in neurodevelopmental disorders (NDDs). This review aims to provide a comprehensive overview of advancements in research pertaining to the microbiota-gut-brain axis in NDDs. Furthermore, we analyzed both the current state of research progress and discuss future perspectives in this field.